Sistem Pakar Dalam Mengidentifikasi Penanda Minat Karakteristik Ekstrakurikuler Berbasis Case Based Reasoning - Sisi Hendriani; Gunadi Widi Nurcahyo; Y Yuhandri (Jurnal Informasi dan Teknologi, 2021)
Extracurricular is an additional activity at school whose purpose is to help develop students' talents, talent is defined as an innate ability which is a potential that needs to be developed and trained. Extracurricular selection is chosen by the students themselves without the intervention of teachers or parents so that students often only follow the majority of their friends' wishes. Knowing the extracurricular characteristics of students through the type of learning will make students' self-development more focused. This study uses the Case Based Reasoning method with similarity calculations which has 4 stages, namely retrieve (rediscover old similar cases), reuse (make old cases as solutions to new cases), revise (evaluate proposed solutions) and retain (store new cases). on a case basis) to determine the type of learning of students which will then be known to be suitable extracurricular activities due to the condition of the psychological development of children during the junior high school (SMP) level who tend to make the wrong choice or just participate in choosing something, especially in terms of selection. extracurricular at school. The learning styles are classified into six learning styles, namely Linguistic, Kinesthetic, Interpersonal, Musical, Naturalist and Logical Mathematics which are then adapted to the extracurricular fields at school. This study identifies the characteristics of student interest using student data at SMP Negeri 17 Padang, the results of similarity 66% for interpersonal learning style, 0% for kinesthetic learning style, 6% for musical learning style, 14% for natural learning style, 0% for logical mathematics learning style and 13% for linguistic learning style. The resulting expert system can help students quickly provide an appropriate extracurricular overview.